Digital Literacy Praxis in Diploma III Cadets of Marine Transportation Management Study Program at Merchant Marine Polytechnic of Sulawesi Utara - Silalahi, Aliong; Agnesia, Floren; Irawan, Santun (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This research was conducted to investigate how the praxis and effectiveness of digital literacy praxis in diploma III students of the Marine Transportation Management study program at the Merchant Marine Polytechnic of Sulawesi Utara. Methodology: The type of approach used in this study is a mix method approach, which is by combining quantitative and qualitative research. Quantitative research was used to calculate the number of correspondent responses. Qualitative research is the activity of exploring and developing the phenomena that occur. Usually, qualitative research makes a complex picture, examines words, detailed reports from the respondent's point of view and conducts a study on the situation that occurs. Main Findings: From the findings and discussions that have been carried out regarding the praxis of the four pillars of digital literacy in Marine Transportation Management students in the 3rd semester at Merchant Marine Polytechnic of Sulawesi Utara, 2 (two) conclusions can be reached. The first conclusion is that digital skills are the pillars in digital literacy that are most mastered by Marine Transportation Management students in the 3rd semester at Merchant Marine Polytechnic of Sulawesi Utara. Students are very proficient in using digital devices and utilizing the internet network in processing information. Novelty/Originality of this study: In common ways, the result of this research will offer valuable information to set up appropriate solution to make learning materials in order to empower and enrich students skills on literacy understanding and its practice.